Enduring the earthquake: Rediscovery of the critically endangered Mesilau stream toad, Ansonia guibei Inger, 1966 (Anura, Bufonidae) and its conservation implications - Evan S.H. Quah; PAUL YAMBUN IMBUN; Sze Huei Yek (Magnolia Press, 2024)
The Mesilau Stream Toad (Ansonia guibei) is a species of bufonid endemic to Sabah, Borneo, and restricted to a single mountainous location above 1600m in elevation. The species is only known from the type locality, the Mesilau watershed on Mount Kinabalu. An earthquake in 2015 resulted in massive landslides, causing extensive damage to the species’ habitat at Mesilau. This event was expected to have caused significant population declines of at least 80% or even the potential extinction of the species. A survey in 2017 at Mesilau failed to locate any individuals, which resulted in it being listed as Critically Endangered by the IUCN. Surveys in late 2023 to reassess the status of the species and its habitat resulted in the rediscovery of a single subadult specimen of A. guibei. Tadpoles of the species were recorded in the main Mesilau River and one additional tributary, which indicates the species survives and is breeding. Studies are ongoing to collect more ecological data on the species and determine its current distribution. The data gathered will be used to construct a robust conservation plan for the species. Nevertheless, these preliminary observations bode well for the future of the species as it demonstrates that it is resilient and capable of recovering from the damages caused by the earthquake.